Transient expression of full-length and mature nattokinase in Nicotiana benthamiana reveals early necrosis from full-length form and functional activity of the mature enzyme - Wang, Kevin; Mason, Hugh; Hall, Kylie; Slone, Ethan; Tackett, Kylie; Wang, Nan (Frontiers in Plant Science, 2025)
Nattokinase is a potent fibrinolytic enzyme widely used in the treatment of cardiovascular diseases for its ability to directly degrade fibrin and plasmin substrates, effectively dissolving blood clots. In this study, both full-length and mature forms of the nattokinase coding sequence were transiently expressed in Nicotiana benthamiana using a modified Bean Yellow Dwarf Virus (BeYDV) replicon system. Overexpression of the full-length (pre-pro) construct resulted in severe leaf necrosis within 2.5 days post-infiltration (dpi), with electrolyte leakage analysis indicating an 83.5% loss of membrane integrity by 3 dpi. In contrast, the mature form of nattokinase was successfully expressed without early cytotoxicity and exhibited strong caseinolytic and fibrinolytic activity, reaching 22,500 FU/g—comparable to commercial standards. These findings demonstrate the feasibility of producing biologically active nattokinase in plants and highlight the potential of plant-based expression systems as scalable, cost-effective platforms for therapeutic enzyme production.